Внутренние связанные колебания и экспоненциальные волны переноса в цилиндрическом стержне - Ванин, Виктор Антонович; Григорьев, А. А.; Дериенко, А. И. (НТУ "ХПИ", 2009)
За допомогою лінійної теорії пружності та потенціалів Герца вивчаються експоненціальні хвилі переносу, що розповсюджуються по циліндричному стрижню. Підтверджені та уточнені результати застосування класичної теорії тонких стрижнів. Отримані хвилі переносу імпульсу, що не описуються класичною теорією.

At use of the linear theory of elasticity and Hertz potentials the exponential waves of translation extended on a cylindrical core are investigated. The results of the use of the classical theory of thin cores are confirmed and specified. The waves of the impulse transfer which are not described by the classical theory are gained.
Keywords: линейная теория упругости; экспоненциальные волны; цилиндрический стержень; потенциалы Герца; короткие волны; теория тонких стержней; волны переноса импульса